1997
DOI: 10.2136/sssaj1997.03615995006100030039x
|View full text |Cite
|
Sign up to set email alerts
|

Automated Chamber Measurements of Methane and Nitrous Oxide Flux in a Flooded Rice Soil: II. Fallow Period Emissions

Abstract: Methane and N2O are radiatively important gases that are emitted from waterlogged soils. Automated chamber measurements of CH4 and N2O fluxes were carried out at the International Rice Research Institute in the Philippines in flooded rice (Oryza sativa L.) and fallow rice fields 24 h a day between December 1992 and April 1994. This period included three 5‐ to 11‐wk rainfed fallow periods. During the first two fallows, the soil was generally aerobic, and moderate amounts of NO3 accumulated (7–20 kg NO3‐N ha‐1).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 0 publications
3
35
0
Order By: Relevance
“…The early drainage or soil drying after only a few days of N application resulted in high N 2 O emissions due to dry conditions in DS, although, the Philippines' recommendation during fertilizer application is to maintain 3-5 cm ponded water. As observed in many previous field studies (e.g., Bronson et al 1997;Sander et al 2014;Sun et al 2016;Tariq et al 2017), substantial N 2 O fluxes were often observed after N fertilizer topdressing during temporal drained periods under AWD and AWDS, especially for DS. In other words, as reported by Zou et al (2005), keeping flooded soil conditions could minimize the N 2 O flux peaks observed after the topdressing.…”
Section: Effects Of Water Management On Ghg Emissionssupporting
confidence: 75%
See 1 more Smart Citation
“…The early drainage or soil drying after only a few days of N application resulted in high N 2 O emissions due to dry conditions in DS, although, the Philippines' recommendation during fertilizer application is to maintain 3-5 cm ponded water. As observed in many previous field studies (e.g., Bronson et al 1997;Sander et al 2014;Sun et al 2016;Tariq et al 2017), substantial N 2 O fluxes were often observed after N fertilizer topdressing during temporal drained periods under AWD and AWDS, especially for DS. In other words, as reported by Zou et al (2005), keeping flooded soil conditions could minimize the N 2 O flux peaks observed after the topdressing.…”
Section: Effects Of Water Management On Ghg Emissionssupporting
confidence: 75%
“…Because rice root system would not be well established by then, ebullition was a plausible pathway of the CH 4 emission (Schutz et al 1989). Bronson et al (1997) reported that CH 4 production was enhanced after an extended saturated soil condition. Corton et al (2000) observed the initial high peaks of CH 4 flux at the vegetative stage due to the anaerobic decomposition of rice straw incorporated.…”
Section: Effects Of Water Management On Ghg Emissionsmentioning
confidence: 99%
“…Inundation in wetland rice promote anaerobic conditions, whereby N 2 O is more likely to be re-consumed before being emitted from the soil (Davidson 1991). High N 2 O emissions after drainage of the paddy field (Bronson et al 1997) are not included in most measurements in our data set. Low N 2 O emissions from grassland may be related to the long growing season of grass and higher N uptake than in crops with shorter growing periods.…”
Section: Agricultural Fieldsmentioning
confidence: 99%
“…The NO 3 − is denitrifi ed when the soil becomes saturated by rain or irrigation . Rain in the fallow period between rice crops stimulates the emission of N 2 O (Bronson et al, 1997c;Abao et al, 2000), which is associated with nitrifi cation-denitrifi cation. Appreciable NO 3 − can accumulate during the fallow period particularly when periodic rains help maintain a favorable soil water content for nitrifi cation .…”
Section: Nitrifi Cation-denitrifi Cationmentioning
confidence: 99%